Meningkatkan Hasil Belajar PAKat dan Gotong Royong Melalui Model PBL Fase A SD Negeri 04 Aris - Agnes Sri Mulatsih (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The purpose of this classroom is to determine aspects of learning outcomes and mutual cooperation as well as measure the results of target achievements through the Problem Based Learning model in Class II Phase A of SD Negeri 04 Aris, Capkala District, Bengkayang Regency, West Kalimantan Province. The research subjects of the students were II grade students at SD Negeri 04 Aris, totaling 6 students, consisting of 6 male students. The object of the research is the result of learning and mutual cooperation of students in Catholic Religious and Character lessons on the material “The Birth of Jesus” and “Jesus Presented in the Temple of God”. The data collection techniques are observation, tests and documentation. The results of the research showed that there was an increase in learning outcomes and mutual cooperation for class II students on the material “The Birth of Jesus” and “Jesus was Presented in the Temple of God” by applying the Problem Based Learning model. The increase in learning outcomes and mutual cooperation is evidenced by the average score of learning outcomes in Cycle 1 which was 66,67% and Cycle 2 was 86,67%, the scoreincreased by 20% while the average score of mutual cooperation in Cycle 1 was 61,5% and Cycle 2 is 81,5%, score increases 20%.